The Use and Toxicity of the Filler Reinforcement in Rubber Industry - ศิริวงศ์ โฉมศรี (KKU Science Journal, 2015)
The use of particulate fillers to achieve the desired reinforcement has widely been acknowledged by rubber industry. Generally, carbon black (CB) and precipitated silica (PSi) are most widely used as reinforcing filler. The presence of reinforcing filler is essential to reach longer-wearing products, improved tyre strength and longevity and, especially for silica, alleviated greenhouse gas emissions of the vehicles using these tyres. Although, the use of fillers in the rubber industry has been safe for decade, however, these fillers are being associated with man-made nanomaterials, which are being substantially investigated for their potential adverse health effects and are the subject of pending regulatory controls. This article provides the information of the use of fillers in the rubber industry, differentiates the filler materials used by the industry toward their particle sizes, and summarizes the state of knowledge based on the toxicological properties of silica and carbon black fillers.